Toxoplasma Gondii-Derived Exosomes: A Potential Immunostimulant and Delivery System for Tumor Immunotherapy Superior to Toxoplasma Gondii [Corrigendum] - Zhao LX; Sun Q; Wang C; Liu JJ; Yan XR; Shao MC; Yu L; Xu WH; Xu R (International Journal of Nanomedicine)
Zhao LX, Sun Q, Wang C, et al. Int J Nanomedicine. 2024;19:12421—12438. Page 12423, line 9, the text “by inducing macrophage polarization and stimulating T cells.38,39” should read “by stimulating macrophage and T cells.83”. Page 12429, lines 1-3, the sentence “Another study revealed that T. gondii secretes exosomes after host invasion, and the exosomes present T. gondii antigens to T cells either directly or via antigen-presenting cells, which activate T cells and immune responses.39” should be removed. Page 12435, References section, the following references should be removed from the reference list. 38. Schorey JS, Cheng Y, Singh PP, Smith VL. Exosomes and other extracellular vesicles in host-pathogen interactions. EMBO Rep. 2015;16:24–43. doi:10.15252/embr.201439363 39. Théry C, Duban L, Segura E, Véron P, Lantz O, Amigorena S. Indirect activation of naïve CD4+ T cells by dendritic cell-derived exosomes. Nat Immunol. 2002;3:1156–1162. doi:10.1038/ni854 The authors apologize for these errors.